Influence of summertime mesoscale convective systems on the heat balance and surface mixed layer dynamics of a large Amazonian hydroelectric reservoir - Curtarelli, Marcelo P.; Ogashawara, Igor; Araujo, Carlos A. S.; Alcantara, Enner H. [UNESP]; Lorenzzetti, Joao A.; Stech, Jose L. (Amer Geophysical Union, 2014)
We evaluated the impacts of summertime mesoscale convective systems (MCS) on the heat balance and diel surface mixed layer (SML) dynamics of the Brazilian Amazon's Tucurui Hydroelectric Reservoir (THR). We used a synergistic approach that combines in situ data, remote sensing data, and three-dimensional (3-D) modeling to investigate the typical behavior of the components of the heat balance and the SML dynamics. During the study period (the austral summer of 2012-2013), 22 days with MCS activity were identified. These events occurred approximately every 4 days, and they were most frequent during January (50% of the observations). An analysis of local meteorological data showed that when MCS occur, the environmental conditions at THR change significantly (p-value<0.01). The net longwave flux, which was the heat balance component most strongly impacted by MCS, increased more than 32% on days with MCS activity. The daily integrated heat balance became negative (-54 W m(-2)) on MCS days, while the balance was positive (19 W m(-2)) on non-MCS days. In response to the changes in the heat balance, the SML dynamics changed when a MCS was over the THR. The SML depth was typically 28% higher on the days with MCS (approximate to 1.6 m) compared with the days without MCS (approximate to 1.3 m). The results indicate that MCS are one of the main meteorological disturbances driving the heat balance and the mixing dynamics of Amazonian hydroelectric reservoirs during the summer. These events may have implications for the water quality and greenhouse gas emissions of Amazonian reservoirs.
Keywords: Tropical reservoirs; Amazon; Mesoscale convective system; Heat balance; Surface mixed layer dynamics